An overview of 33 years of trends in space weather research: a bibliometric analysis (1988-2021) - Asraf Hairuddin, Muhammad; Zainuddin, Aznilinda; Iffah Abd Latiff, Zatul; Mohd Anuar, Nornabilah; Dalila Khirul Ashar, Nur; Sharizat Hamidi, Zety; Hassan Nordin, Abu; Ihsan Mohd Yassin, Ahmad; Yoshikawa, Akimasa; Huzaimy Jusoh, Mohamad (Institute of Advanced Engineering and Science, 2025)
Space weather (SpW) is a phenomenon caused by a variety of solar events and has the potential to disrupt infrastructure systems and technology, putting them at risk. Despite SpW’s immense impact, there has been a notable absence of bibliometric analysis studies to understand the research trends, regional distribution, social structure, conceptual structure, and knowledge gaps. This review synthesized scopus documents of SpW domain from 1988 to 2021. In this study, three tools were used, such as Microsoft Excel, VOSviewer, and Harzing’s Publish or Perish for statistical analysis, graphical presentation, and citation metrics, respectively. Based on the 3,956 articles, roughly 70% of the articles were published in the last ten years, reveals a rapid growth in SpW research. The study discovered that China ranked third in publication volume, following the United States and the United Kingdom with Russian Federation following closely in fourth place. This study also presents six key findings, including the growth pattern of publications, contributions, and authorship collaboration by countries, most productive and influenced authors, co-authorship status, most influenced journals and articles, research cluster and new SpW subtopics discovered. These findings provide useful insight and aid in the advancement and progress of this field.